Marital relationship pada pasangan usia muda: Scoping review - Putu Ayu Dina Saraswati; Andari Wuri Astuti; Mohammad Hakimi (Universitas Ahmad Dahlan, 2020)
There is nine percent of women aged 15-19 who have married or living together in Indonesia, one percent of women divorced in the age group of 15-19 years. This scoping review aimed to review the evidence about the marital relationship among young couples in developing countries. Arksey and Malley framework was applied involving identifying relevant evidence; identifying review questions; identifying relevant evidence; study selection; charting data; and collating, summarizing and reporting the data. PRISMA flowchart is used to show the process of searching the literature. Results of the review showed that there were ten pieces of evidence included and processed within a review. These four themes emerged, i.e. marriage decision-makers for the young couple; changes in the marriage practice of young couples; unpreparedness pregnancy on a young couple; the perspective of young couples about marital relationship. The young married couple will face many environmental and social problems with the result that they must be able to adapt to deal with the stresses and pressures that arise in their family life.